TEACHING LISTENING COMPREHENSION THROUGH VOICE OF AMERICA (VOA) SPECIAL ENGLISH BROADCAST - Nuryadi, Wahyu Dwi Savitri; Susilawati, Endang; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Artikel ini berkaitan dengan pemahaman siswa terhadap listening comprehension. Voice of America (VOA) special English broadcast digunakan sebagai materi dalam pengajaran listening comprehension kepada siswa kelas X Sekolah Menengah Atas (SMA) Muhammadiyah Ketapang pada tahun Akademik 2011/2012. Tujuan melakukan penelitian ini adalah untuk mengetahui seberapa efektif penggunaan VOA special English broadcast dalam pengajaran listening comprehension. Metode penelitian artikel ini adalah pra - eksperimental dengan siswa XC sebagai sampel. Sebagai hasilnya, ditemukan bahwa perhitungan dari effect size (ES) adalah 1.27, itu berarti bahwa pengajaran listening comprehension melalui VOA special English broadcast sangat efektif. Kata Kunci : Voice of America, listening comprehension Abstract: This article concerned with the students listening comprehension. Voice of America (VOA) special English broadcast was used as material in teaching listening comprehension to the tenth grade students of sekolah menengah atas (SMA) Muhammadiyah Ketapang in Academic year 2011/2012. The purposed of conducting the research was to know how effective the use of VOA special English broadcast in teaching listening comprehension. The method of this article is a pre experimental research with students of XC as the sample. As the result, it was found that the effect size (ES) calculation is 1.27; it means that teaching listening comprehension through VOA special English broadcast is highly effective. Key words: Voice of America, listening comprehension